Cross-curricular Connections of Music Culture and Other Subjects in Croatian Elementary Schools - Amir Begić; Jasna Šulentić Begić; Ivan Vodopić (University of Maribor Press, 2023)
Music lessons provide many opportunities for cross-curricular connections with other subjects. As part of the study, research was conducted on a sample of 110 teachers of Musical Culture in elementary school. The aim of the research was to find out the teachers' views on the implementation of cross-curricular connections between the teaching of Musical Culture and other subjects, the frequency and methods of conducting such teaching, as well as any statistically significant differences between teachers in the attitudes towards and implementation of cross-curricular connections with regard to sociodemographic variables. We believe that the results of this research indicate the need for more intensive implementation of cross-curricular connections between the teaching of Musical Culture and other subjects.